2016
DOI: 10.1039/c5cc05342k
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkylchain conjugation as a new tactic for enhancing cell permeability of peptide nucleic acids (PNAs) via reducing the nanoparticle size

Abstract: Perfluoro undecanoyl chain conjugated peptide nucleic acids (PNAs) show 2.5 to 3 fold higher cellular uptake efficiency in NIH 3T3 and HeLa cells compared to simple undecanoyl PNAs. Fluorination of PNAs leads to the formation of lower size (∼100-250 nm) nanoparticles compared to larger size (∼500 nm) nanoparticles from non-fluorinated PNAs, thereby improving the efficiency of cell penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…These thiols were used in combination with 1H,1H,2H,2H-perfluoro-1-decanethiol (HF8) or 1H,1H,2H,2H-perfluoro-1-octanethiol (HF6) as the fluorinated components. The uptake by HeLa cells and the cytotoxicity of these charged H-/F-mixed monolayer AuNPs were compared to those of charge neutral NPs obtained by using the thiols N-1-{2-[2-(2-methoxyethoxy)ethoxy]ethyl}-8-sulfanyloctanamide (HC8TEG) and 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecafluoro-10-(methoxy-PEG550)decan-1-thiol (HF8PEG), Figure 1B. The synthesis of the thiols HMDDS, HMDA, and HTMDA is reported in the Supporting Information (SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These thiols were used in combination with 1H,1H,2H,2H-perfluoro-1-decanethiol (HF8) or 1H,1H,2H,2H-perfluoro-1-octanethiol (HF6) as the fluorinated components. The uptake by HeLa cells and the cytotoxicity of these charged H-/F-mixed monolayer AuNPs were compared to those of charge neutral NPs obtained by using the thiols N-1-{2-[2-(2-methoxyethoxy)ethoxy]ethyl}-8-sulfanyloctanamide (HC8TEG) and 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecafluoro-10-(methoxy-PEG550)decan-1-thiol (HF8PEG), Figure 1B. The synthesis of the thiols HMDDS, HMDA, and HTMDA is reported in the Supporting Information (SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4,5 Soft NPs made of peptide nucleic acid (PNA) conjugated to perfluoroundecanoyl chains display a 3-fold higher cellular uptake by HeLa cells with respect to undecanoyl PNA. 6 Soft NPs obtained by complexation of polyampholites with perfluorododecanoic acid were found to hinder the formation of amyloid fibrils, while hydrogenated analogues were not effective. 7,8 Furthermore, in a thermodynamic analysis of water-soluble fluorinated AuNPs as putative drug delivery systems, we found that nanoparticles displaying fluorinated ligands on their surface interact with drug-like guests with higher affinity than hydrogenated NPs of similar structure.…”
Section: ■ Introductionmentioning
confidence: 97%
“…There are reports that the cells can uptake 0.5–8 µm particles by phagocytosis [ 23 ]. Particles around 500 nm can also enter the cytosol via cellular permeability [ 24 ]. It is known that particles bigger than 200 nm are usually filtered by the liver, while smaller particles can be quickly cleared by the kidney or through extravasation [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of ASOs to molecules that can bind to certain ligands in the cell can improve their cell uptake and internalization. Small hydrophobic molecules, such as cholesterol [83], lipids [84], or fluorinated chains [85,86] may increase ASOs stability and their membrane permeation. Multivalent N-acetylgalactosamine (GalNAc) conjugation is another important way for ASOs delivery to hepatocytes [87].…”
Section: Strategies To Improve Asos Cell Targeting and Overcome Toxicitymentioning
confidence: 99%